IMPROVEMENT OF BUSINESS PROCESS MECHANISMS OF SEWING AND KNITTING ENTERPRISES (Proceedings of International Educators Conference, 2023)
The article examines the role of improvement of its organizational and economic mechanisms in increasing the effectiveness of the main business processes in sewing and knitting enterprises.